A genome-wide association study of plasma total IgE concentrations in the Framingham Heart Study - Granada, Mark; Wilk, Jemma B.; Tuzova, Marina; Strachan, David P.; Weidinger, Stephan; Albrecht, Eva; Gieger, Christian; Heinrich, Joachim; Himes, Blanca E.; Hunninghake, Gary M.; Celedón, Juan C.; Weiss, Scott T.; et al. (Journal of allergy and clinical immunology, 2012)
Atopy and plasma IgE concentration are genetically complex traits, and the specific genetic risk factors that lead to IgE dysregulation and clinical atopy are an area of active investigation. We sought to ascertain the genetic risk factors that lead to IgE dysregulation. A genome-wide association study (GWAS) was performed in 6819 participants from the Framingham Heart Study (FHS). Seventy of the top single nucleotide polymorphisms (SNPs) were selected based on P values and linkage disequilibrium among neighboring SNPs and evaluated in a meta-analysis with 5 independent populations from the Cooperative Health Research in the Region of Augsburg cohort, the British 1958 Birth Cohort, and the Childhood Asthma Management Program cohort. Thirteen SNPs located in the region of 3 genes, FCER1A, signal transducer and activator of transcription 6 (STAT6), and IL13, were found to have genome-wide significance in the FHS cohort GWAS. The most significant SNPs from the 3 regions were rs2251746 (FCER1A, P = 2.11 × 10−12), rs1059513 (STAT6, P = 2.87 × 10−8), and rs1295686 (IL13, P = 3.55 × 10−8). Four additional gene regions, HLA-G, HLA-DQA2, HLA-A, and Duffy blood group, chemokine receptor (DARC), reached genome-wide statistical significance in a meta-analysis combining the FHS and replication cohorts, although the DARC association did not appear independent of SNPs in the nearby FCER1A gene. This GWAS of the FHS cohort has identified genetic loci in HLA genes that might have a role in the pathogenesis of IgE dysregulation and atopy. It also confirmed the association of the known susceptibility loci FCER1A, STAT6, and IL13 for the dysregulation of total IgE.